Trends in the Development of International Transport Cooperation in Uzbekistan - Ishonkulova Feruza Asatovna (International Journal on Integrated Education, 2023)
This article examines the creation and development of international transport cooperation, the need for a strategy for entering new markets, and the results of the transport forum of the SCO member states.